Мышление в русской языковой картине мира (предварительные заметки) - Uryson, Elena (Wiener Slawistischer Almanach, 2024)
The main object of the proposed work is two Russian words related to the description of the mental sphere: the verb to think in the process meaning and the noun thought. The task of the work is to reveal some specific features of the representation of thinking recorded in the Russian language and, thus, in the Russian linguistic picture of the world. It will be demonstrated that the achievements of early twentieth century psychology in cognizing the thinking process coincide in an unexpected way with the linguistic representation of thinking – as if the language anticipated these discoveries by fixing in its semantic system some subtle, nonobvious features of thinking to which psychology paid attention only a little more than a hundred years ago. The description of the selected fragment of the linguistic picture of the world offered here corresponds well to the extra-linguistic reality we observe, explaining the easy change of attitudes and beliefs occurring among the masses of people in crucial epochs.